Academic Data Warehouse Modeling in Higher Education Using Nine-Step Design Methodology - Sihombing, Denny Jean Cross (Journal of Information Systems and Informatics, 2022)
Data and information are essential in various fields today, as well as in the field of education, especially in universities. Some universities already have information systems that support data and information needs. However, the system has not been integrated, so it cannot provide data and information needs quickly and in an integrated manner. Information systems in universities are still primarily departmental because each was built at a different time and uses another platform. The departmental nature of this information system causes inaccuracies and inconsistencies of data that drive the information produced in reports and data reused in transactions to be invalid. Invalid data, in the end, also impacts decision-making taken by management. This study aims to develop a data warehouse at a university to integrate academic data using a star schema. The method used is the Nine Step Methodology. The result of this research is data warehouse architecture used in the academic field; fact tables and ERDs have been designed at the current stage of designing a Prototype of the Study Program Performance Sheet (LKPS).